Changes and Clinical Significance of PIVKA-II in Hepatitis E Patients - Chen, Youran; Yang, Yanyan; Li, Shanshan; Lin, Minghao; Xie, Xueting; Shi, Huifang; Jiang, Yuchun; Zheng, Sijie; Shao, Hui; Yang, Naibin; Lu, Mingqin (Frontiers in Public Health, 2022)
Increased protein induced by vitamin K absence or antagonist-II (PIVKA-II) levels had been widely reported in patients with HCC and chronic hepatitis. However, the role of PIVKA-II in hepatitis E is unclear. The aim of this study was to clarify the changes related with PIVKA-II and its clinical significance in hepatitis E. We enrolled 84 patients with hepatitis E hospitalized in two hospitals from December 2019 to June 2021. The levels of serum PIVKA-II and related serological indicators in the patients were determined to elucidate the role of PIVKA-II in hepatitis E. We observed that 59.51% (50/84) of patients showed an increase in PIVKA-II levels. Compared with normal PIVKA-II group (<32mAU/L), patients in elevated PIVKA-II group (>32mAU/L) had much higher serum TBIL, DBIL, IBIL, and TBA levels (p<0.05 for each). Compared with slightly elevated PIVKA-II group (32-125 mAU/L), patients in significantly elevated PIVKA-II group (>125mAU/L) had much lower serum albumin, ALT, AST levels and longer days for hospital stay (p<0.05 for each). The association of PIVKA-II with TBIL and DBIL was an inverted U-shaped curve with an inflection point at 199.1mAU/L). The association of PIVKA-II with IBIL was a U-shaped curve with an inflection point at 18.6 mAU/L while the association of PIVKA-II with albumin was an inverted U-shaped curve with an inflection point at 18.6 mAU/L. With the improvement of the disease, PIVKA-II levels gradually decreased and finally returned to normal. This trend was consistent with that of bilirubin, and a peak appeared in the third week. Therefore, findings from our study show that the increase in PIVKA-II levels can be related to the degree of hepatic insufficiency in patients with hepatitis E, wherein PIVKA-II levels are transiently increased, and the trend of change can be related to the disease course.